2006
DOI: 10.1177/0002716206292266
|View full text |Cite
|
Sign up to set email alerts
|

The One-Step Flow of Communication

Abstract: This analysis explores the transformation of public communication in the United States from a two-step flow of messages passing from mass media through a social mediation process, to a one-step flow involving the refined targeting of messages directly to individuals. This one-step flow reflects both a transformation in communication technologies and fundamental changes in the relations between individuals and society. Opinion leaders who played a pivotal role in the two step paradigm are increasingly less like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
117
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(124 citation statements)
references
References 41 publications
1
117
1
5
Order By: Relevance
“…While recent research has emphasized how media outlets and other key communicators of collective and connective actions use the available tools of personalization to address participants in social movements directly (e.g. Bennett and Manheim, 2006;Bennett and Segerberg, 2012), the Table shows that In order to facilitate further interpretation, it is useful to analyze the conditional distributions that can be calculated from the joint distribution in Table 3. Figure III The conditional frequencies from left to right (normalized on the right-hand marginal of Table 3) show the constitution of the average mentions in a message (how frequently does the type on the left-hand side in Figure III mention the type on the right-hand side).…”
Section: 971 (100%)mentioning
confidence: 99%
“…While recent research has emphasized how media outlets and other key communicators of collective and connective actions use the available tools of personalization to address participants in social movements directly (e.g. Bennett and Manheim, 2006;Bennett and Segerberg, 2012), the Table shows that In order to facilitate further interpretation, it is useful to analyze the conditional distributions that can be calculated from the joint distribution in Table 3. Figure III The conditional frequencies from left to right (normalized on the right-hand marginal of Table 3) show the constitution of the average mentions in a message (how frequently does the type on the left-hand side in Figure III mention the type on the right-hand side).…”
Section: 971 (100%)mentioning
confidence: 99%
“…Hindman, 2009). Campaign strategists now reach citizens in real time, with no mediation of journalists (Bennett and Manheim, 2006), and their commentary appears to indeed attract attention and activity on the part of the political Twitterverse. The spin room may be quiet after the debate -a period that may now be the provenance of Twitter humorists and wits -but it is alive and well during it, now in real time.…”
Section: Coproducing or Coopting?mentioning
confidence: 99%
“…Recent studies have shown that social media can play this role [9,25], although Bennet and Manheim [1] point out that traditional opinion leaders may be playing a less important role in the fragmented hybrid media environment of the internet, and Weeks, Ardèvol-Abreu and Gil de Zúñiga [89] describe the increasingly important role of "prosumers," or highly active social media users who play a role of filtering and news transmission to others. In the social-media era, many news stories are passed on to others via friendship networks with varying goals [38] that are not necessarily aligned with what traditional media considers newsworthy, with the maintenance of social capital being one predominant goal [19,56].…”
Section: Hybrid News and Information Assemblagesmentioning
confidence: 99%